DEMONSTRASI MAHASISWA INDONESIA DALAM MERESPONS ISU-ISU SOSIAL DI TENGAH PANDEMI COVID-19 - Adhitiya Prasta Pratama; Silkania Swarizona (Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
The emergence of the Covid-19 pandemic has caused various problems because the closure of all public facilities has hampered community activities. However, the pandemic did not stop the enthusiasm of young people particularly university students. Demonstration in the midst of the  pandemic still took place.  Students have an important role in voicing the aspirations of the oppressed people. The injustice towards the lower classes is marked with Ciptaker (Job Creation) Law, procedures of disbursement of JHT (Old Age Security), and the effort to prolong presidential term. The writers described the data descriptively with qualitative method. The goal is to reveal the reasons, motives, and factors surrounding the actions taken by students. The writers conducted literature study and corpus study to obtain the data. Then, the writers applied the theory of social movement and social protest. As a result, it was found that the desire for change and expressing the identity of the nation's youth, and the common goal of students in demonstrating in the midst of a pandemic  were the factors of the demonstration.